2015
DOI: 10.1039/c5ob01418b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and electronic properties of π-extended flavins

Abstract: Flavin derivatives with an extended π-conjugation were synthesized in moderate to good yields from aryl bromides via a Buchwald-Hartwig palladium catalyzed amination protocol, followed by condensation of the corresponding aromatic amines with violuric acid. The electronic properties of the new compounds were investigated by absorption and emission spectroscopy, cyclic voltammetry, density functional theory (DFT) and time dependent density functional theory (TDDFT). The compounds absorb up to 550 nm and show st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…It was shown that expansion of the π-conjugated system provided tunable light absorption reaching up to 700 nm. A similar trend was also observed for progressively expanded N10-butyl substituted flavins [43]. Moreover, the studied materials provided high thermal stability reaching up to 443 • C [42].…”
Section: Introductionsupporting
confidence: 82%
“…It was shown that expansion of the π-conjugated system provided tunable light absorption reaching up to 700 nm. A similar trend was also observed for progressively expanded N10-butyl substituted flavins [43]. Moreover, the studied materials provided high thermal stability reaching up to 443 • C [42].…”
Section: Introductionsupporting
confidence: 82%
“…UV-Vis spectra of FLDA monomer shows absorption bands at λ max = 445 nm and 373 nm (Figure 1A) corresponding to the transitions from the ground state (S 0 ) to the S 1 (λ max ~ 442–450 nm) and S 2 (λ max ~ 360–375 nm) excited states (Heelis, 1982). These bands are red-shifted to ~ 456 nm for the S 0 → S 1 transition and ~ 376 nm for the S 0 → S 2 transition in FLPDA (Figure 1B), which can be explained by an increase in proton donation from PDA (Kotaki et al, 1970) and by electron-withdrawing inductive effects on the flavin moieties due to incorporation into the highly conjugated PDA system (Mataranga-Popa et al, 2015). The fluorescence emission spectra of FLDA and FLPDA are characterized by emission maxima at 527 nm (λ ex = 450 nm), which correlates well to other known flavin compounds (Kotaki and Yagi, 1970), and confirms the presence of flavin moieties in FLPDA NPs (see Figures 1C,D).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the influence of enlarging the π-conjugated system on the optoelectronic properties of flavin derivatives remains less investigated, although shift of the absorption maxima to a longer wavelengths and change of the redox properties of the chromophore and of the extinction coefficient are expected [ 37 , 38 ]. Indeed, it was shown that the enlarging of the fused π-system from the basic N 10-butyl substituted flavin core to the pyrene-attached derivative was accompanied by progressive bathochromic shift in both the absorption (up to 550 nm) and emission (up to 628 nm) spectra and all π-extended derivatives showed intensive emission with quantum yields of up to 80% while they maintained their electrochemical redox behavior analogous to parent flavin [ 39 ]. Despite the aforementioned viability of advanced alloxazine and lumazine derivatives of flavin as the charge-carrier materials for organic electronics only relatively few reports [ 40 , 41 , 42 , 43 ] about optoelectronic behavior are out there.…”
Section: Introductionmentioning
confidence: 99%